Graphdiyne nanosheets as a platform for accurate copper(ii) ion detection via click chemistry and fluorescence resonance energy transfer. Issue 10 (28th January 2021) - Ge, Chenchen; Li, Jiaofu; Wang, Dou; Lv, Kongpeng; Liu, Quan; Shen, Yan; Zhuang, Xiaoqing; Luo, Wankun; Wu, Zongze; Zhang, Yuhua; Shi, Lulin; Liu, Liping; et al.
Abstract : Cu 2+ detection was performed by taking advantage of the fluorescence quenching ability of graphdiyne and the high specificity of click chemistry. Abstract : A novel sensing platform for sensitive detection of copper(ii ) ions (Cu 2+ ) in living cells and body fluids was developed by taking advantage of the excellent fluorescence quenching ability of graphdiyne (GDY) and the high specificity of click chemistry for the first time.